Tailoring the impact response of a spaceframe vehicle structure towards optimum crashworthiness - Ofochebe, Sunday M.; Nwigbo, Solomon C.; Enibe, Samuel O.; Azaka, Onyemazuwa A.; Akuchi, Ikenna J. (International journal of crashworthiness, 2024)
An approach to develop a spaceframe vehicle structure that shows improved structural crashworthiness in frontal impacts is presented in this paper. A baseline model of the vehicle impact system was formulated through preconception of the vehicle size, shape, components' dimension and material. Preliminary evaluation of crash performance of the vehicle structure using the baseline model revealed some avenues to improve on crashworthiness. Wall thicknesses of the crash boxes, the lower fore rails, and the upper fore rails, were identified as design variables. Structural crashworthiness was evaluated at the design steps using appropriate metrics including; global absorbable energy index (GAEI), local absorbable energy index (LAEI) and acceleration severity index (ASI). A multi-objective optimisation problem was solved to maximise LAEI while ASI was minimised subject to the physical constraints of the system. Pareto optimal solutions showing 30-35% improvement on ASI were achieved with a reasonable 3.56-7.14% trade-off on the LAEI.